Gerakan Dakwah Kyai Mardjan Melalui Nahdlatul Ulama Di Tambakrejo Bojonegoro - Lina Amiliya (STAI Bumi Silampari, 2022)
Nahdlatul ‘Ulama is a jam’iyya diniyah wal-ijtima’iyah based on the teachings of Ahlussunnah wa Jama’ah which has the aim of continuing to provide direction for better change to community by broadcasting Islamic religious teachings that are in accordance with the Shari’ah. Therefore, Nahdlatul ‘Ulama can be a bridge to convey the values and teachings of the Islamic religion that is rahmatan lil ‘alamin. To achieve this goal, the proselytizer has an important role in its implementation. The methode used in this research is descriptive qualitative research with the type of field research. The primary data source of this reserach is an interview with Kyai Mardjan. While the collection technique using observation and interviews. The results of the reserach found from interviews with Kyai Mardjan as a da’i or da’wah mover, namely the da’wah movements carried out through Nahdlatul ‘Ulama have covered various aspects of life and have had a large impact or social change on the community, esppecially the Tambakrejo sub-district. The methods he uses vary widely, including the Fardiah method, the bil-Lisan method, the bil-Hal method, the bil-Hikmah method.